1994
DOI: 10.2105/ajph.84.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the duration of work-related disability: a population-based study of Washington State workers' compensation.

Abstract: OBJECTIVES. The purpose of this study was to examine factors predictive of duration of work-related disability. METHODS. Multivariate survival analysis techniques were used to conduct a population-based, retrospective cohort study on a random sample of 28,473 workers' compensation claims from Washington State filed for injuries occurring in 1987 to 1989. The principal outcome measure was length of time for which compensation for lost wages was paid, used as a surrogate for duration of temporary total disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
203
4
12

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(235 citation statements)
references
References 19 publications
16
203
4
12
Order By: Relevance
“…There seems to be general agreement in the literature on the following associations between workplace factors and work disability: heavy physical labour (Borg and Burr 1997;Krause et al 1997Krause et al , 2001Andersson et al 1983;Danchin et al 1982;Dasinger et al 2000;Høgel-und 2000;Lanier and Stockton 1998;Mackenzie et al 1998;Rønnevik 1988) , repetitive or continuous strain, musculoskeletal strain, uncomfortable working position, and crouching (Krause et al 1997), bending, twisting or working in fixed positions (Bergquist-Ullman and Larsson 1977), and construction work (Cheadle et al 1994). All in all, the literature provides broad evidence that high job demands of various forms constitute an important determinant for work disability and disability retirement, while the scientific evidence directly linking occupational factors and more voluntary early retirement is far more scarce: the Danish unemployment insurance system offers the opportunity of retiring at the age of 60, instead of the normal retirement age of 65 (67 for those aged 60 before July 1st 1999).…”
Section: Introductionmentioning
confidence: 94%
“…There seems to be general agreement in the literature on the following associations between workplace factors and work disability: heavy physical labour (Borg and Burr 1997;Krause et al 1997Krause et al , 2001Andersson et al 1983;Danchin et al 1982;Dasinger et al 2000;Høgel-und 2000;Lanier and Stockton 1998;Mackenzie et al 1998;Rønnevik 1988) , repetitive or continuous strain, musculoskeletal strain, uncomfortable working position, and crouching (Krause et al 1997), bending, twisting or working in fixed positions (Bergquist-Ullman and Larsson 1977), and construction work (Cheadle et al 1994). All in all, the literature provides broad evidence that high job demands of various forms constitute an important determinant for work disability and disability retirement, while the scientific evidence directly linking occupational factors and more voluntary early retirement is far more scarce: the Danish unemployment insurance system offers the opportunity of retiring at the age of 60, instead of the normal retirement age of 65 (67 for those aged 60 before July 1st 1999).…”
Section: Introductionmentioning
confidence: 94%
“…A key reason may be that workers' compensation information rarely has a good link to employer size. Some studies have found higher total disability durations at smaller firms, but some studies have failed to support this finding (Hunt and Habeck 1993, Cheadle, Franklin et al 1994, Galizzi and Boden 1996. 26 An earlier RAND study showed that smaller firms were less likely to have formal return to work programs (Seabury et al, 2011).…”
Section: Figure 43 Relative Employment By Quarter Of Injurymentioning
confidence: 99%
“…A associação entre a incapacidade para o trabalho e a idade tem sido reportada na maioria dos estudos e reflete tanto características intrínsecas quanto extrínsecas. Entre as intrínsecas destacam-se as comorbidades, decréscimo hormonal e alteração nas características de colágeno e elastina, típicas do envelhecimento humano 35 .…”
Section: Discussionunclassified